2012
DOI: 10.1371/journal.pone.0029051
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Heterogeneity of Cervical Intraepithelial Neoplasia Grade 3

Abstract: ObjectiveCervical intraepithelial neoplasia grade 3 (CIN3), the immediate cervical cancer precursor, is a target of cervical cancer prevention. However, less than half of CIN3s will progress to cancer. Routine treatment of all CIN3s and the majority of CIN2s may lead to overtreatment of many lesions that would not progress. To improve our understanding of CIN3 natural history, we performed a detailed characterization of CIN3 heterogeneity in a large referral population in the US.MethodsWe examined 309 CIN3 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Furthermore, these risk factors were more strongly associated with progression to CIN3 compared to invasion. This observation is consistent with a previous study of the heterogeneity of CIN3, which showed factors such as parity, OC use, and smoking were not associated with the size of CIN3 lesions, suggesting that they may not play a major role in the later stages of the natural history of cervical cancer [30]. …”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, these risk factors were more strongly associated with progression to CIN3 compared to invasion. This observation is consistent with a previous study of the heterogeneity of CIN3, which showed factors such as parity, OC use, and smoking were not associated with the size of CIN3 lesions, suggesting that they may not play a major role in the later stages of the natural history of cervical cancer [30]. …”
Section: Discussionsupporting
confidence: 92%
“…More advanced and larger lesions are likely to exfoliate more aberrant cells, facilitating the detection of promoter methylation in cervical scrapes. Accordingly, Wentzensen et al 26 and Yang et al 27 recently demonstrated that high-grade squamous intraepithelial lesion cytology and CIN3 colposcopy and biopsy results indicate larger CIN3. The observation that scrapes of women with CIN2/3 and a short-term (<5 years) PHI revealed lower methylation levels compared to lesions with long-term infections indicates that part of the scrapes of women with a short-term hrHPV infection may be scored as 'methylationnegative' when choosing certain thresholds of the respective qMSPs for scoring methylation.…”
Section: Discussionmentioning
confidence: 69%
“…Accordingly, Wentzensen et al . and Yang et al . recently demonstrated that high‐grade squamous intraepithelial lesion cytology and CIN3 colposcopy and biopsy results indicate larger CIN3.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains to be elucidated how clinically relevant the earlier detection of CIN2 and also CIN3 lesions is because small lesions that are not easy to detect with one biopsy are more likely to regress spontaneously than evident lesions [25]. From our data it appears that women who are most likely to benefit from a second directed biopsy are women with HSIL cytology and HSIL cytology is associated with larger CIN2+ lesions than ASCUS or LSIL cytology [23,26,27]. Another approach to look at clinical relevance of earlier detection of disease is that with multiple biopsies it is possible to identify women who have CIN2+ but also women without significant disease.…”
Section: Discussionmentioning
confidence: 81%